Calorimetric effect and thermokinetics in the formation process of a deep eutectic solvent. Issue 3 (4th January 2022) - Lan, Xue; Dong, Yan Tao; Mu, Tiancheng; Lan, Xiao Zheng
Abstract : Thermodynamic and kinetic properties in the formation process of a deep eutectic solvent, ChCl:urea, were investigated. Abstract : For the first time, we report the calorimetric effect and thermokinetics in the formation process of a model deep eutectic solvent (DES), ChCl:urea. Mixing of a 1-to-2 molar ratio of choline chloride and urea shows a rapid endothermic process under stirring. The rate constants and reaction orders are determined by analyzing the thermokinetic curves at several constant temperatures. Low activation energy and activation parameters demonstrate that the formation of this DES is a rapid process. Other thermodynamic parameters are also estimated.